Dreams of falling [compact disc, unabridged] - White, Karen (Karen S.) (Penguin Audio, 2018)
New York Times best selling author Karen White crafts evocative relationships in this new contemporary women's fiction novel about best friends who share a devastating secret, set in the Lowcountry of South Carollina.